Multi Parametric Magnetic Resonance Imaging in Evaluation of Post Operative Breast - ElSayed, Aya Kamal Mohamed; Darwish, Sara Abdelrahman; Mahmoud Dawoud, Mohammed; Sherif, Mohamed Fouad; El Shafaey, Mohamed Hassan (Journal of Neonatal Surgery, 2025)
Background: Multi-parametric magnetic resonance imaging (MPMRI) is essential for assessing regional axillary nodes, finding concealed breast cancer, and figuring out the cancer's spread. Investigating the diagnostic efficacy of multi-parametric breast MRI in the post-operative breast assessment was the aim of this study. Methods: This prospective study included 40 female patients, aged 34 to 77 years, who had post-operative breast conditions. Each patient underwent evaluation using MPMRI. Results: Sensitivity of the kinetic curves for detection of malignant masses was 91.67 % and specificity was 88.89%. Total choline (t-Cho) was significantly lower in benign lesions than in malignant lesions, with a cut - off value of 2, this gives a sensitivity of 83.33%, the specificity 77.78% and accuracy 80.95. The role of Multi parametric MRI in predicting the presence of a tumor was significant, with a high sensitivity (91.67%), specificity (92.86%), along with a significant (P <0.001). These metrics demonstrate MPMRI effectiveness in accurately identifying tumors, offering a reliable diagnostic tool compared to final biopsy results. Recurrence was significantly different between mammography group and MPMRI group (P=0.001). Conclusions: MP MRI demonstrates significant diagnostic accuracy for identifying recurrent breast cancer after breast surgery.